Splenic abscess and multiple brain abscesses caused by Streptococcus intermedius in a young healthy man - Maliyil, Jepsin (Baylor Health Care System, 2011)
We report a case of splenic abscess with multiple brain abscesses caused by Streptococcus intermedius in a healthy young man without any identifiable risk factors, which resolved with percutaneous drainage and antibiotics. Streptococcus intermedius, a member of the Streptococcus anginosus group, is a common commensal organism of the oral cavity and gastrointestinal tract, and it is a known cause of deep-seated infections. Suppurative infections caused by Streptococcus anginosus group are sometimes associated with bacteremia, but hematogenous spread of infection from an occult source leading to concurrent splenic abscess and multiple brain abscesses has never been previously reported in a healthy young individual.